Intraoperative Complications of Posterior (Forceps) Capsulorhexis in Pediatric Cataract Surgery Through Anterior Approach: Intraoperative Complications in Pediatric Capsulorhexis - Jatoi, Asadullah; Shaikh, Noman Ahmed; Mahesar, Mona Liza (Pakistan Journal of Health Sciences, 2023)
Pediatric cataract surgery often involves a posterior capsulorhexis with forceps to prevent posterior capsule opacification, but it is associated with intraoperative complications such as vitreous loss, anterior hyaloid damage, and zonular dehiscence, which require meticulous surgical skill to manage effectively. Objective: To determine Intraoperativeomplications encountered during posterior (forceps) capsulorhexis in pediatric cataract surgery through anterior approach. Methods: This prospective cohort study was comprised up on 50 peadiatric patients having congenital cataract with age up to 12 years who presented at the study setting included in the. Data were analyzed using SPSS 26.0. Results: The study had 52% population as male while 48% were female, with 58% were right eyes 42% were left eyes. Anterior chamber was collapsed in 14 eyes (28%) after initial paracentesis incision while 36 eyes (72%) maintained original position. Forward bulge of posterior capsule was present in 36% of eyes while in 64% forward bulge was absent. Vitreous thrust was found in 38% cases while in 62% there was no vitreous thrust. Clearance of anterior vitreous face was done in 42 eyes (84%). Conclusions: We found that performing posterior capsulorhexis in pediatric cataract surgery through anterior approach is a safe procedure and encountered posterior capsular bulging and vitreous thrust as the most common complications.